Ownership Structure And Leverage On Esg Disclosure: The Perspective Of Stakeholder And Signaling Theory - Gina Patriani Manuputty; Novita Novita; Nurcahyo Imam Fambudi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2025)
The objective of this study is to examine the influence of institutional ownership structure, leverage, and growth opportunities on ESG disclosure within the infrastructure sub-sector during the 2019-2021 period. The research employs an empirical study to test the relationship between independent variables and the dependent variable. The control variable used in this study is firm size, which reflects the condition of a company. The population consists of companies in the infrastructure sub-sector listed on the Indonesia Stock Exchange from 2019 to 2021, with a total sample of 91 companies. The study utilizes secondary data, collected using the purposive sampling method. The results show that managerial ownership structure and corporate leverage have a significant positive effect on ESG disclosure. Institutional ownership tends to reduce the level of ESG disclosure, while growth opportunities, which were expected to support ESG disclosure, demonstrate a negative impact.